Intensive and critical care nursing (Chruchill Livingstone, 1992)
"The aims of Intensive and critical care nursing are to promote excellence of care of critically ill patients by specialist nurses and their professional colleagues; to provide an international and interdisciplinary forum for the publication, dissemination and exchange of research findings, experience and ideas; to develop and enhance the knowledge, skills, attitudes and creative thinking essential to good critical care nursing practice."